Visual Outcomes of Fractionated Radiotherapy in Optic Nerve Sheath Meningioma: A Retrospective Study - Kheir, Valeria; Faouzi, Mohamed; Borruat, François-Xavier (Klinische Monatsblätter für Augenheilkunde, 2019)
Background Optic nerve sheath meningioma (ONSM) is a rare benign tumour of the optic nerve sheath that can lead to blindness if untreated. Radiotherapy is commonly accepted as being the treatment of choice. We conducted a retrospective monocentric study to assess the effect of radiotherapy on visual outcomes and tumour control in patients with ONSM.Patients and Methods The charts of all patients affected by ONSM between 1994 and 2016 were reviewed retrospectively. Inclusion criteria were: having been followed by our department, initial visual acuity (VA) better than no light perception, and stereotactic fractionated radiotherapy. VA (Snellen), colour vision (Ishihara), and visual field mean defect (in dB), as well as ONSM size (on MRI) were compared before and after radiotherapy. Visual function was considered improved if two or more criteria improved, stabilised if none or only one criterion changed, and worsened if two or more criteria worsened. The Wilcoxon signed–rank test was used to assess the effect of radiotherapy (significant if p value < 0.05).Results VA improved or stabilised in 13/16 patients (81.25%), with median VA improving from 0.1 logMAR (8/10) to 0 logMAR (10/10) (p value = 0.0134). Colour vision improved or stabilised in 11/15 patients (73.33%), with median results improving from 5/13 to 12/13 (p value = 0.3212). The visual field mean defect improved in 13/15 patients (86.66%), and the median mean defect (MD) improved from 10 dB to 4 dB (p value = 0.0106). The size of the ONSM diminished or stabilised in 100% of our patients. No adverse events of radiotherapy were either reported or detected.Conclusion Fractionated radiotherapy is a safe procedure and may improve visual function in patients with ONSM.
Keywords: optic nerve sheath meningioma; radiotherapy; visual function